Energy and life cycle impact assessment for xylitol production from corncob - Dasgupta, Diptarka; Sidana, Arushdeep; Ghosh, Prasenjit; Sharma, Tripti; Singh, Jasvinder; Prabhune, Asmita; More, Snehal; Bhaskar, Thallada; Ghosh, Debashish (Journal of Cleaner Production, 2021)
The conversion of biobased feedstocks into energy and value-added chemicals is one main approach to address the current global challenge for waste mitigation through the biorefinery mode. Corncob biomass which is one of the most abundant agricultural residue in India with a high hemicellulose content, can serve as a potential low-cost raw material for food-grade xylitol production. The present study demonstrates a process for xylitol production from corncob biomass with detailed energy and life cycle analysis for viability assessment. The major highlight of the process is the use of microbial fermentation, where biomass-derived D-xylose is converted to xylitol with high selectivity. Overall, 0.502 kg of xylitol crystals could be produced from 3.5 kg of corncob biomass. Simulation analysis revealed that the evaporators are the primary consumers of energy, and the process of heat integration can significantly reduce the energy requirements of the overall process. Environmental impacts of the system evaluated showed emission results of 8.68 kg CO2 equivalent and revealed that marine aquatic and freshwater eco-toxicity are the only possible contributors to the environment. The results suggest that the process would have favourable energy balances, which can be used in pilot plant and heat exchanger network design and operation for xylitol production scale up to 500 L. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: biomass valorization; Life cycle impact assessment; simulation; xylitol